Non-equilibrium dynamics and large deviations in stochastic lattice models via tensor networks - Causer, Luke (2023)
Over the last few decades, numerical tensor networks have revolutionized the study of quantum many-body systems. Despite this success, their application to classical stochastic problems has not yet been extensively explored. This thesis investigates how tensor network methods can be applied to studying the slow dynamics and the dynamical fluctuations of kinetically constrained models used in the modelling of structural glasses.